(untitled) (Boca Raton, 2002)
Presents detailed information on protein-based biopolymer films and coatings. This work provides an overview of the design, technology, properties, functionality, and applications of biopolymer films and coatings (edible and inedible) from plant and animal proteins. It also discusses commercialized and envisioned applications of protein films.
Keywords: Proteins,Chất đạm; Biotechnology,Công nghệ sinh học